Dynamically Unveiling Metal–Nitrogen Coordination during Thermal Activation to Design High‐Efficient Atomically Dispersed CoN4 Active Sites. (10th March 2021) - He, Yanghua; Shi, Qiurong; Shan, Weitao; Li, Xing; Kropf, A. Jeremy; Wegener, Evan C.; Wright, Joshua; Karakalos, Stavros; Su, Dong; Cullen, David A.; Wang, Guofeng; Myers, Deborah J.; et al.
Abstract: We elucidate the structural evolution of CoN4 sites during thermal activation by developing a zeolitic imidazolate framework (ZIF)‐8‐derived carbon host as an ideal model for Co 2+ ion adsorption. Subsequent in situ X‐ray absorption spectroscopy analysis can dynamically track the conversion from inactive Co−OH and Co−O species into active CoN4 sites. The critical transition occurs at 700 °C and becomes optimal at 900 °C, generating the highest intrinsic activity and four‐electron selectivity for the oxygen reduction reaction (ORR). DFT calculations elucidate that the ORR is kinetically favored by the thermal‐induced compressive strain of Co−N bonds in CoN4 active sites formed at 900 °C. Further, we developed a two‐step (i.e., Co ion doping and adsorption) Co‐N‐C catalyst with increased CoN4 site density and optimized porosity for mass transport, and demonstrated its outstanding fuel cell performance and durability. Abstract : In situ high‐temperature X‐ray absorption spectroscopy and atomic level electron microscopy were developed to monitor the structural evolution of the CoN4 site during the thermal activation to elucidate the formation mechanism. 700 °C is a critical temperature to convert inactive Co oxides and metals to active CoN4 sites, and 900 °C yields the Co−N bond with the highest intrinsic activity and four‐electron selectivity.